(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Intelligent groups of people, scientists, planners, and policymakers from various countries have recognised that environmental quality is not always a simple function of nature, as it was in primitive earth. Today, nature's self-regulating mechanisms are inactive. Every developed and emerging country is highly concerned with striking a balance between environmental concerns and economic progress. Dreadful environmental conditions are wreaking havoc on the biological element of these locations' ecosystems. Human beings, as 'one of the most valuable components of the biosphere,' face a constant state of crisis as a result of sullied air, water, and soil degradation. While both water and land pollution are exceedingly harmful, air pollution is unique in its global dispersion of toxins. Air pollution's effect on health is quite complex, as it is caused by a variety of distinct causes, each of which has a unique effect. Not only the ambient air quality in cities is creating worry, but also the indoor air quality in rural and urban locations. The study is limited to the health consequences of declining air quality in Lucknow. Additionally, the purpose of this study is to ascertain the effects of ambient air quality on the health of the residents of the study area.